Pengembangan Pupuk Hayati Mikoriza oleh Petani Hutan Cisangku, Desa Malasari, Kabupaten Bogor - Luluk Setyaningsih; Nengsih Anen; Dwi Agus Sasongko; Azi Gunawan; Bambang Supriyanto (Institut Pertanian Bogor, 2023)
The success of revegetation in the context of forest land rehabilitation and post-mining land reclamation is often often caused by constraints due to marginal land conditions, such as high acidity/alkalineity, low organic matter content, and low availability of macro nutrients. Mycorrhiza Biofertilizer (MB) is one alternative technology that has been reported to be able to increase the success of the rehabilitation. Forest farmers, as one of the actors in forest rehabilitation activities, do not yet have sufficient knowledge and skills in developing biofertilizer such as MB. The objectives of theis community services were to introduce and improve forest farmer about the MB, as well as to establish the demonstration plot for MB development. The result showed that field training and counseling on mycorrhiza and its benefits, as well as the manufacture of mycorrhizal biofertilizers have been carried out in Cisangku, Malasari village, Bogor Regency involving Forest Farmers Model Conservation Village (KTH MKK). The counseling and training were attended by 25 forest farmer participants. Based on the postest carried out after the implementation of counseling and training, there was an increase in farmers' knowledge about mycorrhizal and its benefits as well as procedures for developing mycorrhizal fertilizers. The participants wer also satisfied and increased their skill in preparing mycorrhizal culture materials and caring for their selves. The participating farmers were even willing to develop MB independently if they have sufficient skills and know the benefits. The increasing knowledge and skills of forest farmers had an impact on improving the quality of forest farmers in supporting forest rehabilitation and becomes an alternative of additional income.